2011
DOI: 10.2500/ajra.2011.25.3650
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Cosmetic Outcomes of External Approach Septoplasty

Abstract: The external approach for septoplasty is an operation that produces significant improvements in subjective and objective nasal health measures. Although requiring greater training and operative time, it is an appropriate approach for the severely deviated nasal septum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
2
28
0
1
Order By: Relevance
“…Conversely, the Nasal Obstruction Symptom Evaluation offers a more focused assessment of subjective nasal obstruction, where three of five questions directly address obstruction and the remaining two address obstruction‐related quality of life (difficult nasal breathing during exertion and trouble sleeping) . Originally developed and validated for use in patients undergoing nasal septal surgery, the NOSE scale has also been used in functional septorhinoplasty and nasal valve surgery . Of note however, this PROM has not been extensively evaluated for use in FESS for CRS .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the Nasal Obstruction Symptom Evaluation offers a more focused assessment of subjective nasal obstruction, where three of five questions directly address obstruction and the remaining two address obstruction‐related quality of life (difficult nasal breathing during exertion and trouble sleeping) . Originally developed and validated for use in patients undergoing nasal septal surgery, the NOSE scale has also been used in functional septorhinoplasty and nasal valve surgery . Of note however, this PROM has not been extensively evaluated for use in FESS for CRS .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was no significant correlation between the change in PNIF score and change in VAS obstruction score following surgery, for any patient group (see Table 4 and Figure 1). 16 Originally developed and validated for use in patients undergoing nasal septal surgery, 16,17 the NOSE scale has also been used in functional septorhinoplasty 18 and nasal valve surgery. 19 Of note however, this PROM has not been extensively evaluated for use in FESS for CRS.…”
Section: Correlation Of Pnif With Vasmentioning
confidence: 99%
“…The Nasal Obstruction Symptom Evaluation score (NOSE), which specifically evaluates the symptom of nasal obstruction, is a symptom‐specific questionnaire. It has been validated for use in septal, nasal valve and septorhinoplasty surgery . This brief questionnaire consists of five simple questions which are used to rate the burden of nasal obstruction during the past month, with each question being scored from 0 (not a problem) to 4 (severe problem) giving a total score of 20.…”
mentioning
confidence: 99%
“…It has been validated for use in septal, nasal valve and septorhinoplasty surgery. [7][8][9] This brief questionnaire consists of five simple questions which are used to rate the burden of nasal obstruction during the past month, with each question being scored from 0 (not a problem) to 4 (severe problem) giving a total score of 20. It therefore provides another potential useful measurement in determining whether there has been any meaningful subjective change following intervention.…”
mentioning
confidence: 99%
“…The primary analysis is comparison of the comprehensive, validated Sino Nasal Outcome Test-22 (SNOT-22) [23] patient-reported scores at 6 months from randomisation (− 2 weeks to + 4 weeks), with complete follow-up of participants to 12 months post randomisation. SNOT-22 is a commonly employed patient reported outcome measure in the assessment of patients with pathologies of the nose and sinuses [23][24][25][26][27][28][29][30] and was first applied to septoplasty in 2003 [31]. Our PPI work found that patient symptoms mapped better to the SNOT-22 than to the NOSE and that patients preferred the SNOT-22 measure.…”
Section: Primary Outcome Measurementioning
confidence: 89%